(untitled) (World Science, 2018)
This paper considers some problems in tourism sector of Azerbaijan. Author has analysed the statistical dates of tourism in Azerbaijan, investigated problems by Portermethod and SWOT analysis. Author suggests to use marketing strategies for innovation development of tourism sector of Azerbaijan.